Enriching Genomic Resources and Transcriptional Profile Analysis of Miscanthus sinensis under Drought Stress Based on RNA Sequencing - Gang Nie; Linkai Huang; Xiao Ma; Zhongjie Ji; Yajie Zhang; Lu Tang; Xinquan Zhang (International Journal of Genomics)
Miscanthus × giganteus is wildly cultivated as a potential biofuel feedstock around the world; however, the narrow genetic basis and sterile characteristics have become a limitation for its utilization. As a progenitor of M. × giganteus, M. sinensis is widely distributed around East Asia providing well abiotic stress tolerance. To enrich the M. sinensis genomic databases and resources, we sequenced and annotated the transcriptome of M. sinensis by using an Illumina HiSeq 2000 platform. Approximately 316 million high-quality trimmed reads were generated from 349 million raw reads, and a total of 114,747 unigenes were obtained after de novo assembly. Furthermore, 95,897 (83.57%) unigenes were annotated to at least one database including NR, Swiss-Prot, KEGG, COG, GO, and NT, supporting that the sequences obtained were annotated properly. Differentially expressed gene analysis indicates that drought stress 15 days could be a critical period for M. sinensis response to drought stress. The high-throughput transcriptome sequencing of M. sinensis under drought stress has greatly enriched the current genomic available resources. The comparison of DEGs under different periods of drought stress identified a wealth of candidate genes involved in drought tolerance regulatory networks, which will facilitate further genetic improvement and molecular studies of the M. sinensis.